Dynamics of exercise performance and aerobic capacity of athletes in the conditions of combined hypoxia at intake of mixture of BAS - Sukhov, S.; Ivanov, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
At coaching and contesting in mountain terrain, athletes are exposed to combined hypoxia. To minimize its negative effect on athletes, there was developed a mixture of biologically active supplements (BAS) characterized with antihypoxic action. The goal of the study was to test its effect on exercise performance and aerobic capacity of athletes in the conditions of combined hypoxia. Methods: Forty-five elite judoists (22 athletes - experimental group, 23 athletes - control group) have been examined. Both groups were coached with the same program and catered in the same canteen. Athletes in the experimental group received BAS mixture for 8 weeks. Duplicate testing of athletes, at an 8-week interval, was made at breathing with hypoxic mixture with oxygen content 14% that corresponds to altitude 3300 m above sea level. There was assessed the physical performance on bicycle ergometer at a three-step discrete small, submaximal and maximal aerobic load, maximum oxygen consumption (VO2max) and oxygen pulse. Results: At the second testing of the experimental group, the physical performance at heart rates 130, 150, 170 bpm and maximal heart rate has increased, as compared with the first test. In the control group, at heart rates 130 and 150 bpm, the physical performance at the second test was lower, as compared with the first examination, while at heart rates 170 bpm and maximal rate it remained on the same level. Overall volume of work in the experimental group has increased at the second testing from 220±5.0 to 231±5.5 kgm/kg, while in the control group it has slightly decreased from 209.5±5.8 to 202.6±4.0 kgm/kg. Prior to administration of BAS, in the experimental group the VO2max was 2524±98 ml/min (37.72±1.27 ml/kg/min), while after the intake it reached 2598±90 ml/min (38.95±1.25ml/kg/min). In the control group, at the first test the VO2max was equal to 2547±97 ml/min (36.12±1.06 ml/kg/min), and at the second test it reached 2493±95 ml/min (35.41±1.24 ml/kg/min). Oxygen pulse in the experimental group did not change at rest and tended to increase at loads of different aerobic capacity, while the control group has demonstrated an opposite trend. Conclusion: The tested BAS mixture has demonstrated a positive effect on the physical performance, VO2max and oxygen pulse of athletes in the conditions of combined hypoxia.